Entre caminhos e fronteiras: a gênese do conceito de "campo literário" em Pierre Bourdieu e sua recepção no Brasil - Wander Nunes Frota; Enio Passiani (Estudos de Literatura Brasileira Contemporânea)
This paper explores two ways that cross each other at a certain point. The first one delineatesthe genesis of Bourdieu's concept of literary field, which is, in a good measure, tributary to L.L. Schücking’s theorizations. Until now, this in heritance has had little recognition - at least among Brazilian intellectuals. The second way discusses the reception of Bourdieu’s works in the Brazilian academic world and points out the transfer of the concept from its original environment. When the concept crosses national borders in the worldwide process of circulation of ideas, it asks for new readings - some more, others less pertinent - in a continuous effort of updating and adapting the concept to new and different socio-historical circumstances in order to assure its best analytical efficiency.